The fear of miscegenation in matrices and its relevance to Europe today - Penna, Carla [UNESP] (Vandenhoeck & Ruprecht, 2017)
The twentieth century has left a legacy of great wars, totalitarian regimes and atrocities that bequeathed to the twenty-first century not only a new world map that redistributed Europe, but new countries following the reconfiguration of borders. Some of them still suffer the traumatic consequences of unmourned losses which remain entrenched on the social unconscious of persons, groups and societies. Recently, the painful reality of masses of war refugees, unemployment and uncertainty are affecting the matrices and the life of persons and communities. Moreover, new ideologies and right-wing movements are giving space for the expansion of intolerance, fundamentalism, racism, terrorism and polarizations that are threatening the Western world. This paper will introduce the group analytic and psychoanalytic discussion on some of the fantasies involved in ethnic conflicts - the fear of miscegenation, the fear of the breed mix. Fantasies around race, purity, contamination, sacrifice and destruction connected to the idea of mixture of blood will be discussed aiming to understand the recrudescence of fear, hate and massive projections that haunts, but are underway in European matrices.
Keywords: group psychotherapy; miscegenation; matrices; racism; Europe